Akuntabilitas Pengelolaan Keuangan Desa di Kabupaten Kudus (Universitas Negeri Semarang, 2022)
The purpose of this study was to examine the effect of financial statement presentation, financial statement accessibility, internal control system, and competence on village financial management accountability either simultaneously or partially. The population of this study is the village financial manager at the village government in Kudus Regency, with a total of 123 villages. The sample in this study was 34 villages using the slovin technique. Methods of data collection by using a questionnaire. The data analysis technique used descriptive analysis and multiple linear regression analysis. The results showed that the simultaneous and partial presentation of financial statements, accessibility of financial statements, internal control systems, and competence had a positive effect on village financial management accountability.